2010
DOI: 10.1186/1471-2105-11-s1-s46
|View full text |Cite
|
Sign up to set email alerts
|

A fast indexing approach for protein structure comparison

Abstract: BackgroundProtein structure comparison is a fundamental task in structural biology. While the number of known protein structures has grown rapidly over the last decade, searching a large database of protein structures is still relatively slow using existing methods. There is a need for new techniques which can rapidly compare protein structures, whilst maintaining high matching accuracy.ResultsWe have developed IR Tableau, a fast protein comparison algorithm, which leverages the tableau representation to compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 27 publications
(36 reference statements)
0
22
0
Order By: Relevance
“…Other work has shown that tableaux can accurately differentiate folds [57], and can be used for rapid protein structural comparison [3,17] and for protein substructural search [19]. …”
Section: Methodsmentioning
confidence: 99%
“…Other work has shown that tableaux can accurately differentiate folds [57], and can be used for rapid protein structural comparison [3,17] and for protein substructural search [19]. …”
Section: Methodsmentioning
confidence: 99%
“…Such kind of approaches require a criterion for assigning secondary structures to proteins, as belonging to helices, strands or loops or not being part of an SSE at all. Tableau-based methods generally belong to this category, such as SA Tableau Search ( [4]) and IR Tableau ( [5]). The truth about SSE methods is that there is not an exact procedure of assignment and also opinions vary about the precise beginning and end of SSEs ( [4]).…”
Section: Related Workmentioning
confidence: 99%
“…RUPEE is the first, to our knowledge, purely geometric protein structure search 20 to achieve results as good as the best available protein structure searches. Additionally, 21 it can be argued that the kinds of matches that RUPEE does return have more added 22 value than the current state of the art in that with equal scores it is able to return 23 results not biased toward a structure classification hierarchy such as SCOPe or sequence 24 clusters such as the PDB-90. In this regard, RUPEE makes a fundamental contribution 25 to protein structure research that lends itself to being leveraged in existing systems.…”
mentioning
confidence: 99%
“…The processing of text documents within Information Retrieval (IR) 126 has long been used to satisfy these requirements using bag representations. There are 127 two distinct categories of representations for documents, syntactic and semantic, and 128 much of the research applying IR to protein structure search has focused on the 129 latter [20][21][22]. 130 We have adapted the syntactic approach to document similarity, often referred to as 131 shingling [23], to our linear encoding of protein structure.…”
mentioning
confidence: 99%